Prescription Behaviors and Rational Drug Use Awareness Among Future Dentists: A Class-Based Comparative Study - Ocal, Mustafa Cagdas; Talu, Merve Hacer; Baybars, Sumeyye Cosgun; Sofi, Malath (Wiley, 2025)
Objective This study aimed to evaluate dental students' knowledge, attitudes, and behaviors regarding rational drug use (RDU), including antibiotics and analgesics, and to analyze how the educational process influences this awareness.Materials and Methods This cross-sectional study included 408 dental students (170 third-year, 132 fourth-year, and 106 fifth-year students). Data were collected using a structured questionnaire covering demographic characteristics, prescribing habits, patient education practices, drug selection criteria, and the influence of social insurance status. Statistical analyses were performed using IBM SPSS Statistics 22.0. Chi-square test and Fisher-Freeman-Halton exact test were applied, with a significance level at p < 0.05.Results Among the participants, 82.4% reported explaining the disease to patients, though this decreased to 75.5% among fifth-year students (p = 0.001). The evaluation of treatment outcomes dropped from 63.5% in third-year to 35.8% in fifth-year students. Willingness to confirm patient understanding and awareness of social insurance differences also declined in senior years. Notably, the influence of pharmaceutical representatives was minimal across all groups.Conclusion Although students' overall sensitivity to RDU appears to improve, their awareness of treatment costs and systematic patient education practices remains limited. It is recommended that pharmacoeconomics, ethical prescribing, and case-based interactive training modules be integrated into the dental curriculum.
Keywords: attitudes; dental students; drug selection; patient education; rational drug use